Telaah Kritis terhadap Penerapan Pancasila dalam Penanganan Tindak Pidana Terorisme : A Critical Review of the Application of Pancasila in Handling Criminal Acts of Terrorism - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Beby Iman Andri Muliana; Muhammad Fahri Muthahhari; Muhammad Rozaan Annaafi (LITERA: Jurnal Ilmiah Mutidisiplin, 2024)
The application of Pancasila in handling criminal acts of terrorism plays a crucial role in efforts to maintain the security and welfare of Indonesian society. This article aims to analyze the application of Pancasila values in countering terrorism. Through a comprehensive literature study approach, this article assesses the extent to which Pancasila values have been applied to counter terrorism crimes, including how the basic principles of Pancasila such as humanity, social justice, and unity are applied in countering terrorism. With in-depth analysis, this article finds that the values of Pancasila have not been fully implemented in counterterrorism. Through this study, it is hoped that a more effective and integrated solution can be found in fighting terrorism while still upholding the values of Pancasila as a guideline.